2012
DOI: 10.1021/jz3009198
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Wetting Property of Water Confined in Extended Nanospace Simultaneously Measured from Highly-Pressurized Meniscus Motion

Abstract: Understanding fluid and interfacial properties in extended nanospace (10-1000 nm) is important for recent advances of nanofluidics. We studied properties of water confined in fused-silica nanochannels of 50-1500 nm sizes with two types of cross-section: (1) square channel of nanoscale width and depth, and (2) plate channel of microscale width and nanoscale depth. Viscosity and wetting property were simultaneously measured from capillary filling controlled by megapascal external pressure. The viscosity increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(101 citation statements)
references
References 36 publications
(92 reference statements)
4
97
0
Order By: Relevance
“…Such confined water was found to show unique properties differing from bulk water, e.g., higher viscosity, lower dielectric constant, enhancement of liquid conductivity, slower translational molecular motion, and higher protonic mobility compared with bulk water. [30][31][32][33][34][35] These results have suggested that local adsorbed water layers on surfaces and their electrostatic forces affect the collective behavior of bulklike hydration water in the nanochannel spaces.…”
Section: Introductionmentioning
confidence: 95%
“…Such confined water was found to show unique properties differing from bulk water, e.g., higher viscosity, lower dielectric constant, enhancement of liquid conductivity, slower translational molecular motion, and higher protonic mobility compared with bulk water. [30][31][32][33][34][35] These results have suggested that local adsorbed water layers on surfaces and their electrostatic forces affect the collective behavior of bulklike hydration water in the nanochannel spaces.…”
Section: Introductionmentioning
confidence: 95%
“…Here, E is the separation impedance and h is the reduced H. Based on the results of capillary filling experiments, 7 we estimated the separation impedance and permeability for a 2 mm length of nanochannel to be 580 and 5 -6 × 10 -14 m 2 , respectively. For a 10 mm channel, E and K became 13 and 47 × 10 -14 m 2 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The solvent velocity and the viscosity in extended-nano channels can be estimated. 7 The total resolving power of a column corresponds to the total N, which is calculated as N = L/H. Generally, more efficient columns have a smaller H and a greater N.…”
Section: Introductionmentioning
confidence: 99%
“…7a). 47,50,118,119 By utilizing this structure, liquids are easily introduced into the nanofluidic channel by capillary filling. 47 The other technique is a pressure-driven method, where the pressure is controlled via the liquid pressure on the microfluidic channel section, which is connected to the nanofluidic channel (Fig.…”
Section: ·2 Liquid Introduction and Flow Controlmentioning
confidence: 99%
“…By combining the capillary introduction and pressure-driven flow technique, the capillarity and liquid viscosity have been simultaneously measured. 119 Using a similar concept, Shui et al reported two-phase junctions in nanofluidic channels for small-droplet formation. 122 Recently, an improved version of the pressure-driven flow method, where solenoid valves are installed for pressure regulation and pressure control is realized with a 10-ms temporal resolution, was reported.…”
Section: ·2 Liquid Introduction and Flow Controlmentioning
confidence: 99%